2017
DOI: 10.3390/cryst7090281
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Evolution of Ag-Alloyed PbTe-Based Compounds and Implications for Thermoelectric Performance

Abstract: Abstract:We investigate the microstructure evolution of Ag-alloyed PbTe compounds for thermoelectric (TE) applications with or without additions of 0.04 at. % Bi. We control the nucleation and temporal evolution of Ag 2 Te-precipitates in the PbTe-matrix applying designated aging heat treatments, aiming to achieve homogeneous dispersion of precipitates with high number density values, hypothesizing that they act as phonon scattering centers, thereby reducing lattice thermal conductivity. We measure the tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 41 publications
(60 reference statements)
3
20
0
Order By: Relevance
“…10 20 m −3 upon 6 h aging, which decreases down to ∼10 19 m −3 after 48 h aging. 20 This trend was associated with the nucleation of Ag 2 Te precipitates for relatively short aging times, followed by their coarsening observed for longer times. Alongside this microstructure evolution, κ l reaches a minimum value as low as 0.4 W m −1 K −1 at 500 °C upon 6 h aging at 380 °C due to intensive phonon scattering by a high number of precipitates, which increases up to 1.2 W m −1 K −1 upon aging for longer times.…”
Section: Introductionmentioning
confidence: 95%
“…10 20 m −3 upon 6 h aging, which decreases down to ∼10 19 m −3 after 48 h aging. 20 This trend was associated with the nucleation of Ag 2 Te precipitates for relatively short aging times, followed by their coarsening observed for longer times. Alongside this microstructure evolution, κ l reaches a minimum value as low as 0.4 W m −1 K −1 at 500 °C upon 6 h aging at 380 °C due to intensive phonon scattering by a high number of precipitates, which increases up to 1.2 W m −1 K −1 upon aging for longer times.…”
Section: Introductionmentioning
confidence: 95%
“…This follows a rough estimate based on the Callaway model, as well as on a quantitative model for phonon transport in heterogeneous media superimposing the phonon DOS with the precipitates’ size distribution, which is tested for PbTe using the Debye temperature, sound velocity, and phonon DOS as inputs from DFT . It is found that κl of these Ag‐alloyed PbTe‐based compounds is reduced by controlled nucleation of Ag 2 Te precipitates, exhibiting a number density value as high as 2.7·10 20 m −3 upon 6 h aging at 380 °C, as shown in Figure . This yields a TE figure of merit value of approx.…”
Section: Phase Separationmentioning
confidence: 99%
“…An interesting system exhibiting Widmanstätten Sb 2 Te 3 precipitates residing in a PbTe matrix was thoroughly investigated by Ikeda et al., including all evolution stages of nucleation, growth, and coarsening, with implications for microstructure manipulations to control TE transport coefficients . The phase separation approach is well‐demonstrated for Ag‐alloyed PbTe systems, where doping with 3.3–5.0 at.% Ag results in nucleation of the Ag 2 Te phase in the form of precipitates with different N v values upon aging heat treatments . Particularly for PbTe‐based compounds, N v values adequately larger than 10 20 m −3 are required to initiate effective scattering of acoustic phonons.…”
Section: Phase Separationmentioning
confidence: 99%
“…For single‐phase compounds, this may occur due to the introduction of low energy, non‐dispersive impurity modes into the phonon spectra that significantly impact the propagation of acoustic phonons; this effect is not additive with respect to the impurity concentration in the compound. For two‐phase TE compounds, such non‐monotonous behavior is associated with an entirely different factor, that is, the dual effect of doping atoms as forming agents of both substitutional point defects and nucleation of second‐phase precipitates; when both factors interplay, non‐monotonous trend of κ L occurs . It turns out that this approach of alloying with other elements to modify κ L sometimes yields unpredictable results, rendering the effective manipulation of κ L as a very challenging task that requires deep understanding of atomistic mechanisms enabling dissipation of the energy carried by phonons.…”
Section: Introductionmentioning
confidence: 99%